Circulating miRNA analysis for cancer diagnostics and therapy - Valihrach, Lukas; Androvic, Peter; Kubista, Mikael (Molecular aspects of medicine, 2020)
Successful treatment of cancer depends on early diagnosis and effective monitoring of patients' response to therapy. Traditional tools based on tumor biopsies lack the sensitivity and specificity to capture cancer development in its early phases and are not applicable for continuous monitoring. To overcome these barriers, liquid biopsies have been introduced as a minimally invasive and cost-efficient means of diagnosis with high level of specificity and sensitivity. Traditionally, liquid biopsy markers include circulating tumor cells and circulating tumor DNA. During the last decade, a new promising group of biomarkers has appeared and its utilization for cancer diagnosis and monitoring is intensively studied - the microRNAs (miRNAs). In this review, we provide a comprehensive overview of circulating miRNA analysis. We highlight the importance of sampling and quality control, discuss the technical aspects of miRNA extraction and quantification, summarize recommendations for downstream analysis and conclude with future perspectives. Taken together, we present the current state of knowledge in the field of miRNA analysis in liquid biopsies and the expected development and standardization.
Keywords: nádorové biomarkery; nádory; Quality Control; lidé; Liquid Biopsy; Circulating MicroRNA; řízení kvality; Biomarkers, Tumor; Neoplasms; tekutá biopsie; Humans; Specimen Handling; odběr biologického vzorku; cirkulující mikroRNA